2017
DOI: 10.6000/1927-5129.2017.13.24
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Raised-Bed and Conventional Irrigation Systems for Yield and Water Productivity of Wheat Crop

Abstract: A study was conducted at Drainage and Reclamation Institute of Pakistan (DRIP), Tandojam in a clay loam soil. The treatments include raised-bed irrigation system (T1) and conventional irrigation system (T2). The experiment was laid down using randomized complete block design (RCBD) with three replications. The total area under experiment for each treatment and replication was 1004.65 m2 and 334.88 m2 respectively. Groundwater quality of experimental sight was slightly saline. Results of the experiment showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Previous findings of sowing methods on plant height did not agree with Soomro et al, (2017), who stated that wheat plant height (cm) was higher under the raised bed irrigation system than the traditional irrigation system. And also with Asif et al, (2020) indicated that there was a significant difference in plant height between the treatments where the highest numbers obtained in bed sowing (104 cm), followed by ridge sowing (103 cm) and then flat sowing (98 cm) in the growing period 2015-16.…”
Section: Crop Water Productivitymentioning
confidence: 68%
“…Previous findings of sowing methods on plant height did not agree with Soomro et al, (2017), who stated that wheat plant height (cm) was higher under the raised bed irrigation system than the traditional irrigation system. And also with Asif et al, (2020) indicated that there was a significant difference in plant height between the treatments where the highest numbers obtained in bed sowing (104 cm), followed by ridge sowing (103 cm) and then flat sowing (98 cm) in the growing period 2015-16.…”
Section: Crop Water Productivitymentioning
confidence: 68%
“…Moreover, these results are in accordance with the findings of Bhuyan et al (2012), who concluded from their study that water use efficiency and crop productivity for production were higher in bed planting over conventional method. In the same direction, Soomro et al (2017) proved the superior effect with planting on raised bed over conventional irrigation systems for yield and water productivity.…”
Section: Discussionmentioning
confidence: 86%
“…The higher reduction in pH, EC and buildup in organic carbon was recorded under moisture regime 1.2 IW/CPE (I5) applied as seven irrigations and minimum was recorded under moisture regime at CRI stage (I1) where applied only one irrigation during the entire growth period". [21,22,23,24,25,26].…”
Section: Soil Ph Ec and Ocmentioning
confidence: 99%